Internationalization of Ethical Values in Toba Batak Ceremonies: An Anthroplinguistic Perspective - Siregar, Arjuna Junifer; Tampubolon, Flansius; Situmorang, Rahel Theresia Rodame; Tifany (Raja Zulkarnain Education Foundation, 2025)
This study aims to examine the process of internalization of ethical values in Toba Batak traditional ceremonies through an anthropolinguistic approach. Traditional ceremonies are symbolic spaces where language, ritual actions, and kinship relations interact and represent cultural values. This study employed a descriptive qualitative method, with data collection techniques involving analysis of ritual texts used in various ceremonies, such as mangulosi, mangarapot, and mangulosi boru. The results show that ethical values such as somba marhula-hula, manat mardongan tubu, and elek marboru are internalized through traditional speech, kinship arrangements, and material symbols used in ceremonial processions. The anthropolinguistic analysis indicates that ritual language functions not only as a means of communication but also as a mechanism for reinforcing social norms passed down through generations. Furthermore, the internalization of ethical values in the younger generation occurs through the repetition of traditional language formulas, the strengthening of the role of Dalihan Na Tolu in the social structure, and direct participation in family ritual processions. This research confirms that Toba Batak traditional ceremonies serve a crucial role as a medium for the reproduction of moral and ethical values, as well as an instrument for preserving cultural identity amidst the tide of modernization. These findings contribute to the development of anthropolinguistic studies and a deeper understanding of the relationship between language, culture, and ethics in Toba Batak society.